REMOTE SENSING AND GIS-DRIVEN MODEL FOR FLOOD SUSCEPTIBILITY ASSESSMENT IN THE UPPER SOLO RIVER WATERSHED - Mohd Hairy bin Ibrahim (Tanjung Malim, 2024)
REMOTE SENSING AND GIS-DRIVEN MODEL FOR FLOOD SUSCEPTIBILITY ASSESSMENT IN THE UPPER SOLO RIVER WATERSHED by Mohd Hairy bin Ibrahim